If One has the Floor, does One also need to Dance? Topology, Choreology, and the Structure of Digital Space - Vučković, Marko (Imaginations, 2024)
Marcello Vitali-Rosati, in the essay “The Writer is the Architect” complimented by other works, provides a two-part thesis. The first argues that space is a chiasmic structure (as inside-outside); and the second argues that this structure reveals the productive role of the subject in constructing digital space (as architect). The essay here seeks to elucidate this logic and to expose it to a Lacanian critique: that it is a hysterical discourse unable in principle to emancipate digital spaces because it entails a purely immanent subject—in short, a subject which is solely product, not producer, of digital space